Ngayo’: Ilongots’ Communal Ritual Transition to Manhood. - Songcayawon, jesse; Ines, Allaine Jae; Ibanez, Jeriel; Perdido, Jonathan; Ytang, Feliciano (12th International Scholars Conference 2025, 2026)
This study investigates how engagement with symbolic rituals, artifacts, and practices during the Ilongot Ngayo’ rite of passage shapes masculine identity construction for adolescent males. Through interpretive analysis of ethnographies, findings reveal how condensed summary symbols crystallize cultural ideals that are elaborated through conceptual models and behavioral protocols. Modes of performative engagement with potent symbols facilitate internalization of norms, actively fusing masculine identities. The research elucidates specific sociocultural mechanisms linking granular symbolic elements to identity transformation. Findings address gaps in conceptual frameworks regarding enculturation processes. Examining localized rituals illuminates universal dynamics of adolescent development. Further practice-based analyses of rituals and identity transitions are recommended.